Globalization in world history - Stearns, Peter N. (Themes in world history, 2017)
"In this revised edition of globalization in World History, Peter Stearns explores the roots of contemporary globalization, examining shifts in the global flow of people, goods and ideas as early as 1000 CE. Exploring how four moments in history have accelerated the process of globalization, Stearn's narrative details how factors such as economics, migration, disease transmission, culture, the environment, and politics have influenced the nature of globalization as we understand it today" --Provided by publisher.